The Comprehensive Research of the Road Acoustic Screen with Absorbing and Diffusing Surface - KAMISIŃSKI, Tadeusz Marek; KINASZ, Roman; SZELĄG, Agata; RUBACHA, Jarosław; PILCH, Adam; FLACH, Artur; BARUCH, Katarzyna (Archives of Acoustics, 2015)
The paper presents the new solution to a road acoustic screen consisting of elements which are highly diffusing and simultaneously resistant to weathering, but also characterised by a sound absorption. There is described the comprehensive research of such the road acoustic screen with absorbing and diffusing surface. The study includes screen’s resistance to wind load and snow removal, impact tests and measurements of some acoustic parameters.